Adsorção de corante alaranjado de metila aplicando hidróxidos duplos lamelares de Ca/Fe suportado em biochar de serragem de eucalipto - Cruz, Victória Chaves (2023)
Contamination of water resources is a topic much discussed by society due to the serious problems it entails for public health. Among several pollutants, dyes represent the largest group of organic contaminants. In view of this, it is imperative that new materials are developed that have good removal capacity and low production cost. In view of these needs, in the present study wood remains from Eucalyptus saligna were used for the production of activated charcoal. The material was pyrolyzed, physically activated with CO2 and chemically activated with CaFe/HDL impregnation. Then, the obtained material called biochar/CaFe-HDL was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), x-Ray diffraction (XRD) and area analysis techniques, surface (BET). Sequentially in the adsorption, the influence of pH, the adsorption kinetics, the chemical equilibrium and the thermodynamic study were evaluated. The results obtained in relation to the characterization of the material showed a good impregnation of CaFe/LDH in the CO2-activated biochar, which obtained a surface area of 156.28 m².g¹ . The adsorbent dosage was set at 0.5 g.L-¹ and pH 2.15 was defined as the ideal pH. The adsorption kinetics fit better to the pseudo-first order (PFO) model, while the adsorption isotherms fit better to the Brunauer-Emmett-Teller (BET) model. The maximum adsorption capacity was 397.79 mg.g-¹, found at 30 °C. The adsorptive process was considered exothermic, favorable and spontaneous. The results of this study showed that CaFe/LDH supported on CO2 activated biochar showed excellent performance, thus being considered an excellent potential adsorbent for MO removal.